1997
DOI: 10.1677/jme.0.0190173
|View full text |Cite
|
Sign up to set email alerts
|

Expression of neurotrophin-3 in the growing velvet antler of the red deer Cervus elaphus

Abstract: Antlers are organs of bone which regenerate each year from the heads of male deer. In addition to bone, support tissues such as nerves also regenerate. Nerves must grow at up to 1 cm/day. The control of this rapid growth of nerves is unknown. We examined the relative expression of neurotrophin-3 (NT-3) mRNA in the different tissues of the growing antler tip and along the epidermal/ dermal layer of the antler shaft of the red deer Cervus elaphus, using semi-quantitative reverse transcription-polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Very little is known, however, about nerve regeneration and antler innervation during antler renewal. A previous study from our group [12] revealed that neurotrophin-3 (NT-3), a nerve trophic factor, is widely expressed in the growing antlers. NT-3 expression levels are closely correlated with the density and pattern of innervation of different antler tissue types, being highest in the segment immediately subjacent to the tip and lowest in the cartilage layer.…”
Section: Introductionmentioning
confidence: 99%
“…Very little is known, however, about nerve regeneration and antler innervation during antler renewal. A previous study from our group [12] revealed that neurotrophin-3 (NT-3), a nerve trophic factor, is widely expressed in the growing antlers. NT-3 expression levels are closely correlated with the density and pattern of innervation of different antler tissue types, being highest in the segment immediately subjacent to the tip and lowest in the cartilage layer.…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids are organic component velvet topped the content of nutrients, the highest glycine; amino acids are the basic components of living organism tissue cells for life events play a pivotal role. If the body lacks any kind of essential amino acids, it can cause physiological dysfunction, affecting the normal antibody metabolism [18], leading to disease. Similarly, if the body lacks certain non-essential amino acids, it will produce antibodies metabolic disorders.…”
Section: The Contents Of Total Phospholipids Reducing Sugar and Totamentioning
confidence: 99%
“…The unique natural regeneration activity of deer antlers signifies there are probably growth factors for cartilage, vascular, nervous, epidermis and other tissues (Garcia et al 1997;Ko et al 1986;Roh et al 2010). Recently, the components and pharmacological effects of deer antlers have been examined.…”
Section: Introductionmentioning
confidence: 99%